SOCIAL SUPPORT AMONG PUERPERAL AT RISK: ASSOCIATION WITH SOCIODEMOGRAPHIC AND CLINICAL CHARACTERISTICS - Carvalho, Fernanda Fernandes de; Petersen, Ane Gabriele Poli; Tronco, Caroline Sissy; Casagrande, Denise; Rodrigues, Francini de Oliveira; Griep, Rosane Harter; Kolankiewicz, Adriane Cristina Bernat (Cogitare Enfermagem, 2024)
Objective: To assess the association between perceived social support and sociodemographic and clinical characteristics. Method: A cross-sectional study was conducted in a maternity hospital northwest of Rio Grande do Sul/Brazil from November 2021 to April 2022. A sociodemographic and clinical characterization questionnaire and a social support scale were used. Descriptive and inferential analysis. Results: Puerperal women with higher education had higher mean scores for emotional support (p=0.015); white women had higher mean scores for material support (p=0.009); and those in stable unions had higher mean scores for emotional support (p=0.0016), emotional support (p=0.035), information (p=0.019) and positive interaction (p=0.032). There were significant differences between the variables in which the pregnancy was planned, in which puerperal women received more material support (p=0.015) and those with systemic arterial hypertension, who received more support and positive interaction (p=0.014). Conclusions: The puerperal women had high social support scores. However, higher scores were observed among those from higher socioeconomic levels, in union, who had a planned pregnancy and hypertension during pregnancy.